Borges y Rulfo: otro diálogo posible - Olea Franco, Rafael (El Colegio de México, 2017)
Reception: February 6, 2017Accepted: May 22, 2017The first group of Mexicans to read Jorge Luis Borges’s work appeared at the beginning of the 1940’s in Guadalajara; among its members were Juan José Arreola and Juan Rulfo, whose narrative work presents traces of the Argentinian writer. Arguing the familiarity of Rulfo with the initial work of Borges, this paper proposes that there is a direct intertextual relationship between the short stories “Hombre de la esquina rosada”, by Borges,and “La Cuesta de las Comadres”, by Rulfo, one which links the narrative style of the two texts to the construction of a specific orality. Reference is also made to the brief prologue that the Argentinian wrote for Pedro Páramo, a novel for which Borges expressed unfailing admiration.